MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI INSTANT ASSESSMENT - Supriyadi, - (Universitas Islam Darul Ulum, 2016)
The purpose of this research was to determine whether the application of the instant assessment can improve the learning achievement in mathematics. This classroom action research conducted in the first state Junior High School Kalitengah Lamongan with the research subjects were the seventh C graders at the first state Junior High School Kalitengah Lamongan in Odd semester in the academic year of 2015/2016. There were three instruments to collect the data, those are (1) observation sheet, (2) questionare sheet, and (3) test sheet. The data obtained from observations and questionnaires were analyzed by descriptive quantitative, means that the success description in the learning process disclosed by persentage. The result showed that the studentsâ achievement in the first cycle (66.73), the second cycle (71.90) and the third cycle ( 80.97). Thus, the instant application assessment could improve the mathematics achievement.